Some Results of Conditionally Sequential Absorbing and Pseudo Reciprocally Continuous Mappings in Probabilistic 2-Metric Space - K. Satyanna; V. Srinivas (International Journal of Analysis and Applications, 2022)
The objective of this paper is to generate two results in probabilistic 2-metric space by using the concepts of conditionally sequential absorbing mappings and pseudo reciprocally continuous mappings. These results stand as generalizations of the theorem proved by V. K. Gupta, Arihant Jain and Rajesh Kumar. Further these two outcomes are justified by supporting examples.